Nahwu Learning for Madrasah Tsanawiyah Students at Islamic Boarding Schools: Pembelajaran Nahwu Pada Siswa Madrasah Tsanawiyah di Pondok Pesantren - Ahmad Syariffudin Yahya; Imam Fauzi (Universitas Muhammadiyah Sidoarjo, 2021)
Nahwu science is a science that is not easy to understand and is one of the branches of science that studies the rules of the Arabic language. As well as Arabic literature is needed to make it easier to learn the science of nahwu. However, there are shortcomings in learning that is applied to formal education, both schools and Islamic boarding schools, causing understanding that is not optimal. This study aims to determine the effectiveness of a method in learning Nahwu Science. This research was conducted at the Pondok Pesantren Ibnu Abbas As-Salafy Beku, Keliwonan, Masaran, Sragen, Central Java. It has a fairly good quality in the science of nahwu. This research uses descriptive qualitative method. Data analysis used in this research are observation, documentation and interviews. The results of the study revealed the findings that the learning of Nahwu by the students of Madrasah Ibn Abbas As-Salafy Sragen with the istimbad research method in Arabic was considered more effective. And applying the rules of Arabic by using Arabic everyday makes the students of Madrasah Ibn Abbas As-Salafy Sragen better understand. the method used is through the istimbad learning method and the results of the Nahwu learning.